2004
DOI: 10.1074/jbc.m402195200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Deactivation of the Estrogen-related Receptor γ by Diethylstilbestrol or 4-Hydroxytamoxifen and Determinants of Selectivity

Abstract: The estrogen-related receptor (ERR) ␥ behaves as a constitutive activator of transcription. Although no natural ligand is known, ERR␥ is deactivated by the estrogen receptor (ER) agonist diethylstilbestrol and the selective ER modulator 4-hydroxytamoxifen but does not significantly respond to estradiol or raloxifene. Here we report the crystal structures of the ERR␥ ligand binding domain (LBD) complexed with diethylstilbestrol or 4-hydroxytamoxifen. Antagonist binding to ERR␥ results in a rotation of the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
96
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 50 publications
(75 reference statements)
6
96
1
2
Order By: Relevance
“…1) diethylstilbestrol (1) and 4-hydroxytamoxifen (2, 4-OHT) profile as ERR␥ inverse agonists (10). X-ray crystal structures of 1 and 2 bound to ERR␥ have been reported, and both structures are consistent with the observed inverse agonism (11). Due to the small volume of the ligand pocket, the receptor undergoes a large conformational change upon binding 1 or 2 that displaces the AF-2 helix resulting in a loss of coactivator binding.…”
supporting
confidence: 58%
“…1) diethylstilbestrol (1) and 4-hydroxytamoxifen (2, 4-OHT) profile as ERR␥ inverse agonists (10). X-ray crystal structures of 1 and 2 bound to ERR␥ have been reported, and both structures are consistent with the observed inverse agonism (11). Due to the small volume of the ligand pocket, the receptor undergoes a large conformational change upon binding 1 or 2 that displaces the AF-2 helix resulting in a loss of coactivator binding.…”
supporting
confidence: 58%
“…Because these receptors have very small ligand biding pockets, endogenous ligand discovery remains unlikely, although synthetic ligands have been developed and ERRα is blocked by diethylstilbestrol, while ERRβ and γ are blocked by tamoxifen (Coward et al 2001;Greschik et al 2002;Willy et al 2004). The activity of ERRs appears to be constitutive, with the ligand binding pocket stably arranged in an active conformation without ligand (Xie et al 1999;Greschik et al 2002;Greschik et al 2004). Because ERRα is widely expressed in adult tissues, especially in tissues that utilize or can utilize fatty acid β-oxidation, many studies have addressed its role in cellular energetics (Luo et al 2003).…”
Section: Errsmentioning
confidence: 99%
“…Therefore, the transcriptional activity of ERR does not depend on the presence of an endogenous agonist. The crystal structure of the ERR -DES complex showed that the binding of DES to ERR results in a conformational change of a single phenylalanine residue (Phe435) which partially fills the ligand-binding pocket in the apo-LBD and thus interferes with the position of His12 in the transcriptionally active LBD conformation (Greschik et al, 2004;Fig. 5d).…”
Section: Cancermentioning
confidence: 99%